METAPHORS IN THE LYRICS OF THE DANCE OF THE GREAT DESTROYER BY FEAST - Julianto, Haekal; Siddiq, Mohammad; Fasha, Julia (Universitas Gunadarma, 2024)
This study explores the use of literary techniques, particularly metaphors, in imaginative writing, with a focus on song lyrics. The research examines the metaphorical elements in the song lyrics of